Cara Menarik Minat Pelanggan Pada Layanan Gadai Emas Syariah Dari Pegadaian Syarah Melalui Strategi Pemasaran - Anisa Mekarsari; Al Amin Sayid HSB; Eftika Nur Alsiyah; Niken Nor Azhari; Tri Rahmawati (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Sharia pawnshops are non-bank financial institutions that operate in accordance with Sharia principles. This research aims to explore sharia gold pawn development strategies and relate them to existing theories, with a focus on SWOT analysis to formulate effective marketing strategies for sharia gold pawn products. Qualitative methods are used with the Sharia Pegadaian customer population. Through SWOT analysis, marketing strategies will be optimized by exploiting strengths and opportunities and minimizing weaknesses and threats.